2019
DOI: 10.1002/jmv.25437
|View full text |Cite
|
Sign up to set email alerts
|

Viral pathogens associated with acute respiratory illness in hospitalized adults and elderly from Zagreb, Croatia, 2016 to 2018

Abstract: Aims: To investigate the viral etiology of acute respiratory infection (ARI) in hospitalized adults and elderly patients in Croatia, compare the prevalence of detected viruses, and to determine clinical characteristics and seasonal occurrence of investigated infections.Methods: From January 2016 to June 2018, a total of 182 adult patients presented with symptoms of ARI and admitted to the hospital were tested for 15 respiratory viruses by multiplex reverse-transcription polymerase chain reaction. Clinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…As pathogens, human adenoviruses (HAdVs) have been isolated from severe infections in both immunocompromised and healthy individuals ( 1 ). Some adenoviruses have been associated with acute infection of the eye ( 2 ), respiratory ( 3 ), and gastrointestinal tract ( 1 ). In rare cases, infections prove fatal, as observed in a recent neonatal infection of species D adenovirus type 56 (HAdV-D56) ( 4 ), among adult patients in New Jersey with HAdV-B7d ( 5 ) and infamously with HAdV-E4, where large epidemics of adenovirus infection have been seen in military recruits ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…As pathogens, human adenoviruses (HAdVs) have been isolated from severe infections in both immunocompromised and healthy individuals ( 1 ). Some adenoviruses have been associated with acute infection of the eye ( 2 ), respiratory ( 3 ), and gastrointestinal tract ( 1 ). In rare cases, infections prove fatal, as observed in a recent neonatal infection of species D adenovirus type 56 (HAdV-D56) ( 4 ), among adult patients in New Jersey with HAdV-B7d ( 5 ) and infamously with HAdV-E4, where large epidemics of adenovirus infection have been seen in military recruits ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of sensitive and technically simple molecular detection assays, especially multiplex PCR, enabled affordable RV detection in line with other common respiratory viruses in clinical samples. Together with coronaviruses, RVs are indeed responsible for majority of upper respiratory tract infection (URTI), but also for substantial rate of LRTIs in all age groups (Lauinger et al, 2013; Zhao et al, 2018, Čivljak et al, 2019). Many studies showed that RV is one of the leading causes of pneumonia, bronchiolitis and other form of severe respiratory disease (Zhao et al, 2018), standing side by side with respiratory syncytial virus (RSV) in children and influenza in elderly (Esposito et al, 2013; Ning et al, 2017; Čivljak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sequences from this study are shown in bold and are indicated with their strain identification number, followed by the accession number. stood [4,24]. HPIV3 is an important causative agent of ARI that can be complicated with pneumonia, especially in immunocompromised and elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Infections caused by HPIV may be sporadic, although outbreaks are frequent. Seasonal variations in the occurrence of HPIV infections are generally seen when serotype-specific rates of infection are analyzed, which are highly dependent on the region [3][4][5]. More specifically, the seasonal infection patterns observed in the northern hemisphere, in countries with temperate climate, are basically absent in tropical and subtropical regions, where there is little variation in infection rates during the year [3,6].…”
Section: Introductionmentioning
confidence: 99%